Socio-cultural factors and female entrepreneurship (2013)
The purpose of this paper is to analyze the main socio-cultural factors that influence women entrepreneurship in Catalonia, using institutional economics as a theoretical framework. The empirical research employs logistic regression models (rare events logit), utilizing data obtained from the Global Entrepreneurship Monitor project (GEM). The main findings highlight that 'fear of failure' and 'perceived capabilities' are the most important socio-cultural factors on the probability of becoming a woman entrepreneur. The research contributes both theoretically, advancing knowledge of the socio-cultural factors that affect female entrepreneurship, and practically, helping in the development of educational programmes and support policies to promote entrepreneurial activity. © 2013 Springer Science+Business Media New York.